THE EFFECT OF CALCIUM HYDROXIDE-PROPOLIS ON THE NUMBER OF MACROFAG CELLS ON THE WISTAR RAT DENTAL WITH PULPA PERFORMANCE - Setyabudi Setyabudi; Devi Eka Juniarti; Ira Widjiastuti; Maughfirah Shintya Fathori (Conservative Dentistry Journal, 2020)
Background: Cellular response of dental pulp to existing lesions, caused by infiltration of inflammatory cells that migrate from blood vessels to the site of injury. Macrophages are the cells that most appear when inflammation occurs. Treatment for maintaining pulp tissue vitality is called pulp capping. Calcium hydroxide as a pulp capping material has the ability to trigger the growth of dentin bridges or remineralization, but calcium hydroxide can induce migration and proliferation of inflammatory cells. Currently the field of dentistry is developing propolis as an alternative pulp capping material. That is because propolis has anti-inflammatory properties. Objective: To analyze the effect of the combination of calcium hydroxide-propolis on the number of macrophage cells in the teeth of wistar rats with pulp perforation. Method: This study used 30 samples of Wistar rats which were preparated until perforation and then divided into 3 groups. The first group continued with filling with cention, the second group continued with application of calcium hydroxide and filled with cention, and the third group continued with the application of combination of calcium hydroxide and propolis and then being filledwithcention. Macrophage cell is calculated histopathologically by using compound light microscope on the 3rd day with 400x magnification. Results: The Kruskal-Wallis test results showed significant differences in macrophages after the combination of calcium hydroxide and propolis (p = 0,000). The combined application of calcium hydroxide and propolis showed higher macrophages than the application of calcium hydroxide and the control group. Conclusion: Application of calcium hydroxide - propolis combination was proven increase the number of macrophage cells in Wistar Rats (Rattus Norvegicus) with pulp perforation